TINGKAT KEPUASAN KONSUMEN TERHADAP ATRIBUT BUAH PEPAYA DI PASAR TRADISIONAL KOTA SURAKARTA - M.Th. Handayani; Ratih Dwi Kartikasari; Nur Husnina Fatin (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
This study aims to determine the level of satisfaction of consumers towards the attributes of papaya in the traditional market of Surakarya City. Data is processed using the CSI (Customer Satisfaction Index) method. The study was conducted from January to March 2020 in Surakarta City with 100 consumers as respondents. CSI analysis is used to measure the level of customer satisfaction through the calculation of consumer ratings of the attributes of indicators attached to an item. The results of the study based on CSI values indicate that the results of consumer satisfaction in traditional markets are classified as satisfied (80,59%). The order of consumer satisfaction with the attributes of papaya in traditional markets is the variable taste, size, level of maturity and price. Consumers are satisfied because the expectations in buying for papaya in traditional markets in the city of Surakarta have been fulfilled.